2022
DOI: 10.1371/journal.pone.0265873
|View full text |Cite
|
Sign up to set email alerts
|

A web-based cross-sectional study assessing the impact of COVID-19 on the mental health of radiology staff in Saudi Arabia

Abstract: The 2019 novel coronavirus pandemic has not only created massive public health issues, it has also produced excessive psychological disorders in healthcare professionals, including radiology staff. The aim of this study is to assess the risk perception and mental health of radiology staff in Saudi Arabia during the COVID-19 pandemic. The researcher asked radiology staff to complete an online Google Forms questionnaire, between June 10, 2020 and June 17, 2020, which contained demographic data and self-designed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…A 2020 study found that although practitioners harboured concerns regarding personal safety and institutional resources, these worries did not deter from their moral obligation to provide care 54. This was consistent with other findings on the challenges practitioners face in balancing their commitments to patients with their commitments to their loved ones 55 56. Another study described participants’ accounts of moral uncertainty as they relate to medical intervention, triage and resource allocation especially in the absence of scientific evidence 57.…”
Section: Discussionsupporting
confidence: 57%
“…A 2020 study found that although practitioners harboured concerns regarding personal safety and institutional resources, these worries did not deter from their moral obligation to provide care 54. This was consistent with other findings on the challenges practitioners face in balancing their commitments to patients with their commitments to their loved ones 55 56. Another study described participants’ accounts of moral uncertainty as they relate to medical intervention, triage and resource allocation especially in the absence of scientific evidence 57.…”
Section: Discussionsupporting
confidence: 57%
“…Working during the pandemic affected MRT mental well-being across the globe as individuals had to cope with irregular shifts, increased radiation exposure, serious risk of contracting the virus, insufficient protective measures and a heavy workload. 34 , 35 , 36 , 37 We are proposing that each level of influence work together in order to create meaningful change. Governments need to ensure policies are not exclusionary and apply to everyone working in the healthcare system which goes beyond the scope of COVID-19.…”
Section: Discussionmentioning
confidence: 99%